Sleeve Gastrectomy Improved TGF-β and IL-10 Expression in Obesity and Diabetes Mellitus Rats - Mukti, Sindhu Nugroho; Prasetyo, Sigit Adi; Shobirin, Muhammad Ali; Rozy, Abdul Mughni; Prajoko, Yan Wisnu; Sagap, Ismail Bin (Diponegoro International Medical Journal, 2024)
Introduction: Atherosclerosis is a cardiovascular disease which is the leading cause of 16% of the world's total deaths. The main comorbidities of atherosclerosis are obesity and diabetes mellitus. One of obesity surgery treatment that is currently very often used is the Sleeve Gastrectomy. Sleeve Gastrectomy is the most effective and significant long-term therapy for weight loss and preventing various comorbidities such as heart disease. This study analyze the effect of sleeve gastrectomy on the expression of atherosclerosis anti-inflammatory cytokines (TGF-β and IL-10) in the abdominal aorta on the process of atherosclerosis in obesity and diabetes mellitus subjects.Methods: An in vivo laboratory experimental study with post-test control group design on 15 male rats (Sprague Dawley) that was randomly divided into 3 groups: K1 (negative control), K2 (positive control with obesity and diabetes mellitus) and P1 (obese and DM rats treated with sleeve gastrectomy). After 10th day of the procedure, we analyze the body weight, fasting blood glucose, and gene expression of TGF-β and IL-10 using the PCR method. Statistical analysis was done using Anova, Kruskal Wallis and Post Hoc LSD.Results: There was significant decrease in body weight (p=0,000) and fasting blood sugar levels (p=0,000) in the P1 compared to the K2. There was significant increase of TGF-β (p = 0,005) and IL-10 (p = 0,002) gene expression in P1 compared to K1 and K2.Conclusion: SG decreased body weight and fasting blood sugar levels of obese and DM subjects. Also improved the expression of atherosclerosis anti-inflammatory cytokines (TGF-β and IL-10) in abdominal aorta.